Design of a new type of self-destruct chip monitoring and execution circuit - Hu Changzheng; Ma Wei; Gao Qingyun; Hu Weibo (Dianzi Jishu Yingyong, 2022)
In the current self-destruction technology, the self-destruction monitoring method is single, the self-destruction execution is long, and the self-destruction is incomplete and unstable, which leads to the low success rate of self-destruction. A real-time monitoring and execution circuit system with both self-destruction monitoring and execution is designed. The circuit system designed two self-destruct monitoring methods, packaging and disassembly and power-on timing, which made the self-destruct monitoring methods more diverse and the results more accurate. At the same time, MOS tube was used as the switching characteristic to reduce the time of self-destruct execution. The experimental results show that the circuit system can carry out real-time monitoring of the working chip through the self-destruct monitoring circuit when the supply voltage is 3.3 V and the storage voltage of tantalum capacitor is 20 V. Meanwhile, the test results show that the time from the monitoring to the self-destruct signal to the start of the self-destruct execution is 0.28 ms.